Multidirectional associations between the gut microbiota and Parkinson’s disease, updated information from the perspectives of humoral pathway, cellular immune pathway and neuronal pathway - Jia, Xiaokang; Chen, Qiliang; Zhang, Yuanyuan; Asakawa, Tetsuya (Frontiers in Cellular and Infection Microbiology, 2023)
The human gastrointestinal tract is inhabited by a diverse range of microorganisms, collectively known as the gut microbiota, which form a vast and complex ecosystem. It has been reported that the microbiota-gut-brain axis plays a crucial role in regulating host neuroprotective function. Studies have shown that patients with Parkinson’s disease (PD) have dysbiosis of the gut microbiota, and experiments involving germ-free mice and fecal microbiota transplantation from PD patients have revealed the pathogenic role of the gut microbiota in PD. Interventions targeting the gut microbiota in PD, including the use of prebiotics, probiotics, and fecal microbiota transplantation, have also shown efficacy in treating PD. However, the causal relationship between the gut microbiota and Parkinson’s disease remains intricate. This study reviewed the association between the microbiota-gut-brain axis and PD from the perspectives of humoral pathway, cellular immune pathway and neuronal pathway. We found that the interactions among gut microbiota and PD are very complex, which should be “multidirectional”, rather than conventionally regarded “bidirectional”. To realize application of the gut microbiota-related mechanisms in the clinical setting, we propose several problems which should be addressed in the future study.